Abundance of Viruses in Marine Waters: Assessment by Epifluorescence and Transmission Electron Microscopy - Hara, Shigemitsu (1991)
Abundance of bacteria and tiny DNA-associated particles in the upper layer of Japanese coastal and offshore waters was evaluated by epifluorescence microscopy with 0.015-μm-pore-size Nuclepore filters. The number of tiny DNA-associated particles was compared with the abundance of virus particles estimated by transmission electron microscopy. Although a large variation in virus abundance (1.2 × 10(6) to 35 × 10(6) ml(−1)) was obtained with the transmission electron microscopy method, the ratio of 4′,6-diamidino-2-phenylindole-reactive tiny particles to viruses was in a rather narrow range (1.0 to 1.6), indicating that the majority of the tiny DNA-associated particles identified by epifluorescence microscopy were actually virus particles. This result implies the possibility of using epifluorescence microscopy for the evaluation of virus abundance in marine environments.